A theory of nuclear disarmament: Cases, analogies, and the role of the non-proliferation regime. Issue 1 (2nd January 2022) - Egeland, Kjølv
ABSTRACT: What might prompt a nuclear-armed state to give up its arsenal? Nuclear disarmament has provided a nominally shared goal for virtually all the world's states for decades, yet surprisingly little effort has been devoted to systematically theorizing its drivers. This article aims to begin filling this void. I proceed in three steps. First, I discuss the conceptual, material, and ideational features of renunciation to arrive at a rudimentary understanding of what, fundamentally, nuclear disarmament as a political process involves. Second, I scope out the empirical evidence on which a general theory of nuclear renunciation might be based. Third, synthesizing the dominant explanations for the cases discussed in the second part, I outline a basic account of nuclear relinquishment and discuss the compatibility of this account with common assumptions about disarmament practice. I conclude that the best evidence available suggests that adversarial politics and stigmatization are necessary conditions for renunciation.